2017
DOI: 10.1098/rspb.2016.2738
|View full text |Cite
|
Sign up to set email alerts
|

Comparing physical and social cognitive skills in macaque species with different degrees of social tolerance

Abstract: Contemporary evolutionary theories propose that living in groups drives the selection of enhanced cognitive skills to face competition and facilitate cooperation between individuals. Being able to coordinate both in space and time with others and make strategic decisions are essential skills for cooperating within groups. Social tolerance and an egalitarian social structure have been proposed as one specific driver of cooperation. Therefore, social tolerance is predicted to be associated with enhanced cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 72 publications
(108 reference statements)
2
60
0
Order By: Relevance
“…Pooling resources across study sites makes it possible to collect data from samples that are large and diverse enough to tackle questions about the phylogeny, ontogeny and internal structure of primate cognition. A number of previous one-off projects managed to achieve such a pooling of resources [11][12][13][24][25][26][27] demonstrating that such large-scale collaborations are feasible. However, these previous initiatives did not establish a long-lasting infrastructure for future studies to build on.…”
Section: The Manyprimates Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…Pooling resources across study sites makes it possible to collect data from samples that are large and diverse enough to tackle questions about the phylogeny, ontogeny and internal structure of primate cognition. A number of previous one-off projects managed to achieve such a pooling of resources [11][12][13][24][25][26][27] demonstrating that such large-scale collaborations are feasible. However, these previous initiatives did not establish a long-lasting infrastructure for future studies to build on.…”
Section: The Manyprimates Projectmentioning
confidence: 99%
“…In addition to the weakness of currently-applied methodological approaches to studying comparative psychology, the analytical approaches used to date also have not been sufficiently sophisticated to adequately compare species' responses to test paradigms. Typically, researchers make inferences about primate cognitive evolution through direct comparisons of cognitive measurements across species [11][12][13]. Using this approach, many comparative facts of primate cognition have been established (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the lone longitudinal study in chimpanzees, Lacreuse et al (2014) tested 38 females on the Primate Cognition Test Battery (PCTB), a 13-item test designed to assess social and physical cognition in nonhuman primates (Herrmann et al, 2007a; Herrmann, Hare, et al, 2010; Herrmann, Hernandez-Lloreda, et al, 2010; Joly et al, 2017; Russell et al, 2011; Schmitt et al, 2011). Lacreuse et al (2014) found very little evidence of age-related decline in overall and physical cognition performance.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of primate species lives in complex social groups, in which interactions range from intense competition to cooperation [1][2][3][4][5] . To adjust their behavior optimally, individuals need to assess not only their own actions and goals, but also other group members' current actions, while taking into account the history of interactions with and between these individuals 4,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…5). Yet, the analysis of reaction time distributions suggests that macaques employed a competitive version of turntaking in which the faster agent selects its own color (insists) while the slower agent follows (accommodates).…”
mentioning
confidence: 99%